2019 International Conference on Computer and Information Sciences (ICCIS) 2019
DOI: 10.1109/iccisci.2019.8716463
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Social Commerce Behavior in Saudi Arabia

Abstract: Social commerce is getting popular all over the world including in the middle eastern countries. The main objective of this work is to identify the factors that influence the purchasing intention and the behavior among the Y generation and millennials in the Kingdom of Saudi Arabia. For this purpose, a hypothetical conceptual model was developed based on proven theories and well-established literature. To test this model, data were collected from 178 university students using an online questionnaire. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Alotaibi [31] highlighted that in terms of m-commerce consumer loyalty, there were no major variations across gender, age, or experience. Razi et al [32] have found that students are actively engaged in social commerce activities, which impact their purchase intentions and behavior positively.…”
Section: Related Workmentioning
confidence: 99%
“…Alotaibi [31] highlighted that in terms of m-commerce consumer loyalty, there were no major variations across gender, age, or experience. Razi et al [32] have found that students are actively engaged in social commerce activities, which impact their purchase intentions and behavior positively.…”
Section: Related Workmentioning
confidence: 99%
“…College students are considered as the most vibrant group in terms of the use of social networking sites due to their technology-education orientated and information seeking as well as multi-tasking nature. The use of social networks for college students creates a lasting environment where according to Razi et al (2017) they feel bonded in terms of closeness and emotionally. Thus they anticipate some form of social and moral support from social network colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media and technology appropriate for aspects of shopping has become a major problem for retailers and related businesses [8]. The number of factors that influence the growth of social commerce is due to the increase of popularity of social media, network notification, social search and online collaborative shopping tools [9].…”
Section: Introductionmentioning
confidence: 99%